Systematic review and classification of: Parent Management Training – The Oregon Model (PMTO) as individual parental guidance (2. ed.) - Stormark, Kjell Morten; Christiansen, Øivin (Ungsinn. Journal of Effective Interventions for Children and Adolescents, 2018)
Background: This paper reviews the effectiveness of the Parent Management Training- The Oregon Model (PMTO) when provided as an individual parent training intervention targeting children with conduct problems. The program comprises weekly consultations of different durations with parents. PMTO was developed at the Oregon Social Learning Center. The Norwegian Center for Child Behavioral Development holds the Norwegian rights. Method: A systematic literature review was undertaken in EMbase, Medline, Psykinfo, NORART, Cochrane, Cristin, NORA, SCOPUS, SweMed to find publications reporting results from relevant trials. During the review, two additional publications were added, yielding a total of 26 publications, of which nine publications based on seven studies assessed PMTO efficiency. Results: PMTO is a well described program with a systematic implementation plan and high program fidelity. The publications draws on the results from one Norwegian and one Icelandic randomized controlled superiority trial, with a Norwegian follow-up study. In addition a Norwegian dissemination study has been conducted. The Norwegian data also forms the basis for comparing the effects in subgroups and with another parent training program (The Incredible Years). Even though the effects of PMTO is mostly small in magnitude, and not entirely consistent, they are clinically significant. High program fidelity is a strength, which enhance implementation of PMTO. Threats to the studies internal validity and questions regarding the measurements, statistical analyses and the external validity represents the main weaknesses in the studies on PMTO outcome. Conclusion: PMTO as an individualized parent supervision program for children with conduct problems is classified at evidence level 5 - Intervention with strong documentation of effect.